2011
DOI: 10.1159/000329502
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Osteonecrosis of the Femoral Head with VEGF<sub>165</sub> Transgenic Bone Marrow Mesenchymal Stem Cells in Mongrel Dogs

Abstract: We evaluated the efficacy of vascular endothelial growth factor 165 (VEGF165) transgenic bone marrow mesenchymal stem cells (BMSCs) for the repair of early-stage osteonecrosis of the femoral head (ONFH) in mature mongrel dogs. This animal model was surgically established by femoral neck osteotomy and subsequent repinning. Twenty-seven dogs (54 hips) were divided into 3 equal-sized groups: a pCI-neo-VEGF165 BMSC group, a pCI-neo BMSC group and a core decompression-alone group. The lipofect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 73 publications
1
53
0
Order By: Relevance
“…The findings of other studies suggested that the treatment with SC-79 (an Akt activator) and Vitamin K2 significantly improved the efficacy of osteogenesis in animals [17, 21]. Furthermore, transgenic overexpression of P-glycoprotein or VEGF165 in BMSCs significantly increased stem cell-induced osteogenesis as well [19, 20]. In addition, SDF-1 was found to be closely associated with osteogenesis and angiogenesis [49, 50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of other studies suggested that the treatment with SC-79 (an Akt activator) and Vitamin K2 significantly improved the efficacy of osteogenesis in animals [17, 21]. Furthermore, transgenic overexpression of P-glycoprotein or VEGF165 in BMSCs significantly increased stem cell-induced osteogenesis as well [19, 20]. In addition, SDF-1 was found to be closely associated with osteogenesis and angiogenesis [49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P-glycoprotein (P-gp) overexpression was found to decrease the risk of steroid-induced ONFH [19]. The latter risk was alleviated by rifampicin likely through enhancing P-gp activity [20], whereas glucocorticoid-induced ONFH was successfully prevented by treatment with Vitamin K2 [21]. Moreover, augment the expression of BMP-2 and BFGF in BMSCs promoted bone repair of ONFH [22].…”
Section: Introductionmentioning
confidence: 99%
“…There are several etiologic risk factors such as trauma [3, 4], excessive corticosteroid use [57], excessive alcohol intake [8], Legg-Calve-Perthes disease [9, 10], etc. Debilitated blood supply to the femoral head commonly leads to necrosis and collapse of the femoral head [11]. In spite of various research efforts and trials, ONFH is still one of the most serious orthopedic problems.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors affecting the choice of treatment are the extent and location of the necrotic area. 24,26 During the procedure for core decompression in patients with ONFH, the defect is filled with morsellized or synthetic bone grafts followed by graft impaction, which creates mechanical and biological conditions for graft incorporation. 21 All of the patients in this study were classified as having either stage I or stage II disease.…”
Section: Discussionmentioning
confidence: 99%